Assessment of Knowledge and Prevalence of antimicrobial use (AMU) among patients in a District Hospital in Abuja, Federal Capital Territory, Nigeria - Idoko, Lucy O; Okafor, Kingsley C.; Lolo, Nomsu S. (European Journal of Applied Sciences, 2023)
Background: Worldwide, antimicrobial use is a major contributor to the development of antimicrobial resistance (AMR), with people and animals serving as the primary drivers. Knowledge of antibiotic rational use includes not only providers' actions in ensuring patients receive appropriate treatment for their condition, at the right dose and duration, but also patients' actions in adhering to the treatment protocols recommended, completing the full course, and not sharing or storing medicines for future use. This study aims to determine the knowledge and prevalence of antimicrobial use among patients in a District Hospital in Abuja, Federal Capital Territory, Nigeria. Methods: This was descriptive, cross-sectional study done in September, 2022 among 400 patients attending outpatient clinic at Maitama District Hospital Abuja's. A multistage sampling technique was used in this study. The data was analyzed using the IBM SPSS 28 (Statistical Package for the Social Sciences) computer software (IBM SPSS Inc. 2021). Ethical approval was granted by Bingham University Teaching Hospital, Jos, Plateau State. Results: The prevalence of antimicrobial use in the last 1 month, 6month and last 1 year was 41.5%, 32.0% and 5.6% respectively. A majority (74.25%) of the participants had gotten a prescription for the antibiotics from a doctor or nurse, 83.75% of them had received advice from a doctor, nurse or pharmacist on how to take the antibiotics while 16.25% of them had not. The antibiotics were sourced pharmacy (70.25%), hospital (22.5%), clinic (4.25%) while 3% stated other sources. Respondents stated that the conditions that can be treated with antibiotics, bladder infection or urinary tract infection (UTI) (75.2%), followed by Skin or wound infection (70.8%), Sore throat (62.4%) and Gonorrhea (55.9%) were the most selected. While other conditions were Cold and flu (48.5%), Fever (33.7%), Malaria (34.2%), Measles (30.7%), Body aches (21.3%), Headaches (11.9%) and HIV/AIDS (11.4%). Two thirds (63.25%) of respondents had good knowledge of antimicrobial use, 17.25% fair knowledge of antimicrobial use, and 19.5% poor knowledge of antimicrobial use. Test of association showed statistical significance for Age (χ² (2, N=400) = 69.56, p < 0.003), Marital status (χ² (2, N=400) = 96.64, p < 0.001) and Education (χ² (2, N=400) = 106.53, p < 0.01). Conclusion: The prevalence of antimicrobial use in the last 1 month was 41.5%, prevalence in last 6 months was 32.0% and in last 1 year was 5.6% respectively.Two thirds of respondents had good knowledge of antimicrobial use, 17.25% fair knowledge of antimicrobial use, and 19.5% poor knowledge of antimicrobial use. Individuals and communities should develop proper health-seeking behavior, such as consulting a physician or a licensed health workers before using antimicrobials.